2019
DOI: 10.1007/s42452-019-1348-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of fuel properties of cottonseed biodiesel and its impact on engine performance and emission

Abstract: Rising level of pollution and extreme rate of depletion of fossil fuels has become a major issue in today's world which requires immediate measures for its prevention. Biodiesel is the potential answer to this threat to environment as being an extremely promising fuel given its adaptability of usage in currently existing engine modules. Out of various oil sources for biodiesel production (Jatropha, Pongamia, Neem, Mahua) Cotton seed oil is one of the prominent source for biodiesel production in India. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Another major obstacle in biodiesel production is associated with feedstock costs, which account for about 60–70% 179 . To reverse the situation and reduce the cost associated with biodiesel production, different alternative feedstocks which are non‐food crops (inedible) like Jatropha curcas , 181 jojoba ( Simmondsia chinensis ), 182 cottonseed ( Gossypium hirsutum ), 183 moringa ( Moringa oleifera ), 184 and others have been exhaustively tested by different researchers.…”
Section: Fruit Waste and Byproduct Valorization Into Biofuelsmentioning
confidence: 99%
“…Another major obstacle in biodiesel production is associated with feedstock costs, which account for about 60–70% 179 . To reverse the situation and reduce the cost associated with biodiesel production, different alternative feedstocks which are non‐food crops (inedible) like Jatropha curcas , 181 jojoba ( Simmondsia chinensis ), 182 cottonseed ( Gossypium hirsutum ), 183 moringa ( Moringa oleifera ), 184 and others have been exhaustively tested by different researchers.…”
Section: Fruit Waste and Byproduct Valorization Into Biofuelsmentioning
confidence: 99%
“…Meanwhile, another study examined the effect of aluminum on a B20 cotton seed oil biodiesel and reported a 10% reduction in brake thermal efficiency and a 15% increase in brake-specific fuel consumption compared to conventional diesel. Furthermore, the presence of metal also increased the nitrogen oxide pollution of biodiesel by 16% (Puniyani et al 2019 ). A comprehensive study of the effect that several transition metals and their metal oxides on biodiesel stability concluded that copper causes the fastest oxidation, while molybdenum and rhenium slower the oxidation process.…”
Section: Oxidation Stability Of Fatty Acid Methyl Estersmentioning
confidence: 99%
“…Nevertheless, the utilization of vegetable oil in diesel engines is sometimes hindered by its high viscosity and the existence of bigger droplets during the combustion process. As a result, a transesterification process was employed in the production of biodiesel with the objective of reducing the viscosity value 27,28,29,30,31) .…”
Section: Introductionmentioning
confidence: 99%